Guided Growth of Horizontal p-Type ZnTe Nanowires - Reut, Gilad (J Phys Chem C Nanomater Interfaces, 2016)
[Image: see text] A major challenge toward large-scale integration of nanowires is the control over their alignment and position. A possible solution to this challenge is the guided growth process, which enables the synthesis of well-aligned horizontal nanowires that grow according to specific epitaxial or graphoepitaxial relations with the substrate. However, the guided growth of horizontal nanowires was demonstrated for a limited number of materials, most of which exhibit unintentional n-type behavior. Here we demonstrate the vapor–liquid–solid growth of guided horizontal ZnTe nanowires and nanowalls displaying p-type behavior on four different planes of sapphire. The growth directions of the nanowires are determined by epitaxial relations between the nanowires and the substrate or by a graphoepitaxial effect that guides their growth along nanogrooves or nanosteps along the surface. We characterized the crystallographic orientations and elemental composition of the nanowires using transmission electron microscopy and photoluminescence. The optoelectronic and electronic properties of the nanowires were studied by fabricating photodetectors and top-gate thin film transistors. These measurements showed that the guided ZnTe nanowires are p-type semiconductors and are photoconductive in the visible range. The guided growth of horizontal p-type nanowires opens up the possibility of parallel nanowire integration into functional systems with a variety of potential applications not available by other means.